Fatal Cryptococcal Meningitis in a Patient With Chronic Lymphocytic Leukemia - Oguzhan Sıtkı Dizdar; Faruk Karakeçili; Belkıs Nihan Coskun; Beyza Ener; Rıdvan Ali; Reşit Mıstık (Mediterranean Journal of Hematology and Infectious Diseases)
Patients with chronic lymphocytic leukemia (CLL) are susceptible to infections, especially opportunistic infections. We have described a patient with CLL who had cryptococcal meningitis. Despite lack of previous immunosuppressive treatment history, the patient experienced serious and fatal fungal infection. Physicians should be alert for a diagnosis of cryptococcal meningitis in patient with CLL who developed fever and headache.